(untitled) (Texas Journal of Medical Science, 2022)
Novel coronavirus infection is known as severe acute respiratory syndrome coronavirus 2 (SARS‑CoV2). Some patients presented with non-respiratory manfestations including neurological nerve involvement has been reported